Gambaran Candida albicans dalam Urine Pasien Diabetes Melitus Perempuan di Puskesmas 1 Denpasar Timur - Ayu Trisnawati; Ni Wayan Desi Bintari; Nyoman Sudarma (Puslitbang Sinergis Asa Professional, 2022)
Candidiasis is fungal infection caused by the Candida sp. generally by Candida albicans. Diabetes mellitus is one of the predisposing factors for C. albicans fungal infection. The risk of infection is increased in women with hyperglycemia which cause high blood sugar level in vaginal. This condition providing an ideal place for fungal growth. This study aims to determine the description of the C. albicans in the urine of women with diabetes mellitus at Public Health Centre (I) East Denpasar. The sampling technique in this study used purposive sampling with a total sample of 30 urine of women with diabetes mellitus at Public Health Centre (I) East Denpasar in December 2021. The examination method used urine culture techniques on Sabouraud Dextrose Agar media, Gram stain and germ tube test. Based on the results of the examination of positive samples, the characteristics of colonies growing on SDA media were smooth, slightly raised on the surface, yellowish white in color, and smelled of yeast. On Gram staining, the results show the presence of oval-shaped blastopores, and purple in color and the germ tube test shows blastopores that form sprouts. In this study, 2 samples (7%) were positive for C. albicans and 28 samples (93%) were negative for C. albicans. Based on the results of the study, patients are expected to always maintain cleanliness (hygiene) in the genital area and maintain body immunity to reduce the risk of fungal infections.